On the language aspect of selected speeches of president Miloš Zeman - Zábranský, Lukáš (Bohemica Olomucensia, 2017)
In the article the author attempts to clarify how to analyse the linguistic aspect of the presidential speeches in terms of the linguistic image of the world. Analysing ceremonial speeches the author analyses the symptoms of sociativity and persuasion, classifies traditional rhetorical devices (among others figures and tropes) and tries to find answers to the question why these forms were used in the given context by the President M. Zeman. Conceptual metaphors are then analysed as specific units emphasizing, misleading or hiding the expressed meaning.
Keywords: Miloš Zeman; democracy; rhetorics; cognitive linguistics; linguistic picture of the world; the president; ceremonial speech